2005
DOI: 10.1080/00224490509552290
|View full text |Cite
|
Sign up to set email alerts
|

Typing, doing, and being: Sexuality and the internet

Abstract: The increasing salience of sexuality on the internet, whether cybersex or use of the internet to make sexual contacts, has focused interest on how internet-mediated sexuality informs social theory. This article reviews social theory and sexuality in relation to the internet, with specific reference to the development of intimacy, the association of texts with sexual scripts, the emergence of cybersexuality as a sexual space midway between fantasy and action, and the question of boundaries and the location of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
118
0
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 13 publications
0
118
0
12
Order By: Relevance
“…Because of all these societal developments, sexuality is in a continuous state of flux (Ross, 2005;Stone, 1995). Several scholars take the stand that we need large sexual behavior surveys to help understand, investigate, and track this modern evolution of sexuality (Gagnon & Simon, 1977;Traeen, Stigum, & Sørensen, …”
mentioning
confidence: 99%
“…Because of all these societal developments, sexuality is in a continuous state of flux (Ross, 2005;Stone, 1995). Several scholars take the stand that we need large sexual behavior surveys to help understand, investigate, and track this modern evolution of sexuality (Gagnon & Simon, 1977;Traeen, Stigum, & Sørensen, …”
mentioning
confidence: 99%
“…2 Remaining unseen and unknown to others online has been thought to make it possible for people to engage in behavior they would not otherwise engage in, not the least in sexually related behavior due to individual, interpersonal, and societal norms of acceptable and unacceptable sexual behavior. 23,24 The results of this study suggest that the offline setting also plays an important role in how the Internet is used for sexual purposes. This would translate directly to the theory of sexual scripts where sexual behavior is determined partly by the setting.…”
Section: Discussionmentioning
confidence: 77%
“…The anonymous setting provided by the Internet has made it possible to overcome or break away with individual, interpersonal, and societal norms regulating sexual behavior in more traditional settings offline. 23,24 It has also been suggested that the level of anonymity influences what sexual activities people engage in on the Internet; the more anonymous an online setting is, the more sexually explicit (or stigmatized) activity can take place. 23 Thus, it is possible that not only the anonymity in online settings influences online sexual behavior, but also the level of privacy in the offline setting from where the Internet is accessed.…”
mentioning
confidence: 99%
“…5 In addition, men and women have been able to consume pornography and to purchase sexual merchandise online without the stigma attached to these behaviours in public settings offline. 6,7 All these forms of behaviours are examples of sexually related online activities, which, according to Leiblum and Döring's definition, capture all sexually related content and activities observable on the internet. 8 Prior research has focussed on sexual activities on the internet as well as on the characteristics of those who use the internet for sexual purposes.…”
Section: Introductionmentioning
confidence: 99%